A propose of pulmonary dysfunction stratification after valve surgery by physiotherapeutic assistance level - Franco,Satiko Shimada (2015)
AbstractObjective:a) to propose and implement an evaluation system; b) to classify the pulmonary involvement and determine levels of physical therapy; c) to check the progress postoperatively.Methods:Patients underwent physiotherapy assessment preoperatively, postoperatively and after 5 days of intervention. They were classified into three levels of care: level 1 - low risk of complication; Level 2 - medium risk; Level 3 - high risk. We used analysis of variance and Kruskal-Wallis and analysis of variance for repeated measures or Friedman. Chi-square test or Fisher for proportions. We considered statistical significance level P<0.05.Results:We studied 199 patients, 156 classified within level 1, 32 at level 2 and 11 at level 3. Thoracoabdominal motion and auscultation changed significantly postoperatively, persisting at levels 2 and 3 (P<0.05). Oxygenation and respiratory rate changed at levels 2 and 3 postoperatively (P<0.05) with recovery at the end. Significant decrease in lung volumes occurred in three levels (P<0.05) with partial recovery at level 1, lung collapse occurred at all levels, with recovery by 56% at level 1, 47% at level 2, 27% at level 3.Conclusion:The proposed assessment identified valve surgery patients who require differentiated physical therapy. Level 1 patients had rapid recovery, while the level 2 showed significant changes with functional gains at the end. Level 3 patients, more committed and prolonged recovery, should receive greater assistance.